PEMANFAATAN LIMBAH KOTORAN SAPI SEBAGAI SOLUSI SOSIAL DAN LINGKUNGAN DALAM PEMBUATAN PUPUK ORGANIK PADAT - Albar Balfaqih Djafara; Nopiana Mozin; Lucyane Djaafar (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
This field activity focuses on the utilization of cow dung waste as a social and environmental solution through the production of solid organic fertilizers. Held on April 16, 2025 at the Mootoduwo agricultural and Rural Self-Help Training Center (P4S) in Huluduotamo Village, this activity involved all members of Class A of the S1 agribusiness Study Program, Faculty of Agriculture, Gorontalo State University and lecturers for citizenship courses. The stages of activities include the preparation and collection of materials (cow dung, rice bran, granulated sugar, EmA11), grinding cow dung using special machines, mixing and composting of materials , regular monitoring and stirring every 3-4 days, and finally, ripening and packaging of fertilizers. The method used is the delivery of material directly in the field, practicum production of organic fertilizers, and group discussions. The results showed success in producing solid organic fertilizer of good quality, characterized by dark brownish color, brittle texture, and no pungent odor after fermentation. The utilization of this waste not only contributes to improving the quality of the environment and soil fertility, but also provides a positive social and economic impact for rural communities through job creation and increased income in line with civic values.